Nutritional, Physical Activity, and Mental Health Interventions to Enhance Cardiovascular Health: A Scoping Review - Elsadai, Elsadai; Trisyani, Yanny; Nuraeni, Aan (Journal of Health and Nutrition Research, 2025)
Cardiovascular disease (CVD) remains the leading cause of mortality globally and in Indonesia, with rising incidence among younger populations due to modifiable risk factors such as poor diet, physical inactivity, and mental health issues. These lifestyle-related factors are increasingly prevalent, yet interventions addressing them are varied and dispersed across the literature. To explore recent nutritional, physical activity, and mental health interventions for the prevention of cardiovascular disease. This study used a scoping review design. Articles were obtained from six databases, EBSCO-host, CINAHL, PubMed, ScienceDirect, Scopus, Taylor and Francis, and Google Scholar, with the major keywords “dietary”, “physical activity”, “mental health”, “cardiovascular disease”, “prevention”. Inclusion criteria included original studies, in English, published between 2015–2025, and the population reviewed was Adults / General population / High-risk individuals (e.g., aged >30, person with history of CVD). Data extraction followed the PRISMA-ScR guidelines. Twelve articles meeting the inclusion criteria showed intervention of prevention of cardiovascular disease. Physical activities such as walking, yoga, and exercise programs effectively improve cardiovascular health and physical fitness. Nutritional approaches like the Mediterranean diet help reduce cholesterol levels and blood pressure. Mental health practices, including meditation and stress management, contribute to lowering anxiety and blood pressure.  This review emphasizes that integrating regular physical activity, a nutritious diet, and mental health support is essential for effectively preventing cardiovascular disease, with personalized approaches playing a key role in helping individuals maintain these healthy habits.